Reading Journal Articles for Thesis Preparation: Voices from EFL Undergraduates - Kasyfur Rahman (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
This paper seeks to explore the undergraduates’ experiences when reading journal articles as references for their thesis composition through a narrative inquiry. Four undergraduates of English Language Education program at UIN Mataram were interviewed to analyze what they encountered when reading such genre. The findings suggest that their experiences mostly circulated around their motivation and challenges, therefore the narratives were focused on these facets. In terms of motivation, these students seemed to be strongly driven by controlled motivation that entailed the need for a model, accessibility and currency, as well as demands from supervisors and institutions. Furthermore, these students also encountered challenges in terms of unfamiliar academic technical terms and vocabulary, boredom due to text complexities, and failed reading strategies. These findings imply the need of scaffolding the reading of journal articles for undergraduates in their final year of study.